2015
DOI: 10.1016/j.soard.2014.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of median surgeon operative duration on adverse outcomes in bariatric surgery

Abstract: Background Evidence suggests that prolonged operative time adversely affects surgical outcomes. However, whether faster surgeons have better outcomes is unclear, as a surgeon’s speed could reflect skill and efficiency, but may alternatively reflect haste. Objectives This study evaluates whether median surgeon operative time is associated with adverse surgical outcomes following laparoscopic Roux-en-Y gastric bypass. Methods We performed a retrospective cohort study using statewide clinical registry data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(24 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…For example, the correlation between SSIs and prolonged operative duration can be attributable to various time-related factors such as prolonged microbial exposure, diminished efficacy of antimicrobial prophylaxis over time, increased tissue retraction leading to tissue ischemia, necrosis, and desiccation, and increased opportunities for violations in sterile technique. 78,[82][83][84][85] In contrast, the increased risk of VTE due to prolonged operative duration has been linked to factors such as increased coagulation, blood stasis, and endothelial damage resulting from longer surgical procedures. [86][87][88][89] Prolonged operative times are also associated with increased surgical team fatigue and extension of anesthesia durationdfactors that enhance the risk for many different types of complications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the correlation between SSIs and prolonged operative duration can be attributable to various time-related factors such as prolonged microbial exposure, diminished efficacy of antimicrobial prophylaxis over time, increased tissue retraction leading to tissue ischemia, necrosis, and desiccation, and increased opportunities for violations in sterile technique. 78,[82][83][84][85] In contrast, the increased risk of VTE due to prolonged operative duration has been linked to factors such as increased coagulation, blood stasis, and endothelial damage resulting from longer surgical procedures. [86][87][88][89] Prolonged operative times are also associated with increased surgical team fatigue and extension of anesthesia durationdfactors that enhance the risk for many different types of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, operative duration has been associated with postoperative morbidity and mortality for a variety of general surgical, vascular, orthopedic, and other procedures. 7 , 21 24 In the setting of spine surgery, Kim et al 25 analyzed 4588 patients from the ACS-NSQIP database who underwent single-level lumbar fusion and showed that increased operative time was associated with stepwise increase in risk of overall complications, medical complications, surgical complications, and transfusions. Additionally, the type of operation as well as operative length is expected to be indirectly related with anesthesia induction and maintenance times, as it dictates the need for invasive monitoring, special patient positioning, and extent of antiseptic preparation.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that it may be caused by individualized perioperative care, which was proven in another surgical disciplines [ 7 , 41 43 ]. In studies by Reames et al, Carter et al, and Dallall et al, researchers concluded that the longer was the operative time, the greater was the risk for prolonged length of stay [ 17 , 18 , 20 ]. The same relationship was found in our study; however, a multivariate analysis revealed that it was contributing less to the risk of prolonged LOS.…”
Section: Discussionmentioning
confidence: 99%